Kinerja Karyawan PT Perkebunan Nusantara VIII Kebun Cibungur Sukabumi Berdasarkan Efikasi Diri Dan Kecerdasan Emosional - Raihan Mughits Shalshabill; Faizal Mulia Z; Dicky Jhoansyah (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This research was conducted to examine the effect of self-efficacy and emotional intelligence on employee performance at PT Perkebunan Nusantara VIII Kebun Cibungur Sukabumi. The method used in this research is an associative method with a quantitative approach. The population in this study were employees of PT Perkebunan Nusantara VIII Kebun Cibungur Sukabumi. The sampling technique used was the method of saturation sampling by distributing questionnaires to 47 employees of the engineering and processing division of PT Perkebunan Nusantara VIII Kebun Cibungur Sukabumi. The results prove that the f-count value is 20.683 (≥ f-table = 3.209) with a significance value of 0.000 (<0.05). So self-efficacy and emotional intelligence simultaneously have a significant positive effect on employee performance. The results also prove that the t-count value of self-efficacy is 3.200 (≥ t-table 2.014) and the t-value of emotional intelligence is 2.991 (≥ t-table 2.014). So it can be concluded that self-efficacy has a significant positive effect on employee performance and emotional intelligence has a significant positive effect on employee performance.Keywords: Self-Efficacy, Emotional Intelligence, Employee Performance